Strong states, weak schools the benefits and dilemmas of centralized accountability - Fuller, Bruce; Henne, Melissa K.; Hannum, Emily (Emerald JAI, 2008)
Civic leaders around the globe now press educators to raise the performance of students and schools. Backed by a colorful array of odd bedfellows - from corporate interests to advocates for the poor - politicians seek to narrow the aims of learning, advance routine curricular packages, and tightly align standardized tests. Why are governments pushing to centrally regulate teaching and learning at this historical moment? Do these accountability mechanisms succeed in boosting student achievement? How are teachers responding to top-down rules, incentives, and the recasting of what knowledge counts inside school? These are the hotly contested ideological and empirical questions asked by this volume's contributors, a rich mix of sociologists, applied anthropologists, and education researchers. As public schools struggle to regain public confidence, political actors eagerly try to look strong and forceful. But do centralized accountability policies lift the motivation of teachers and students? Or, is this reform strategy a brilliant political remedy - but one that makes little difference inside the classroom.
Keywords: School management and organization -- United States.; Educational accountability -- United States.; Educational evaluation -- United States.; Teacher effectiveness -- United States.; Organization & management of education.; Education -- Administration -- General.; elektronické knihy; electronic books